Moebius anthropology : essays on the forming of form - Handelman, Don (Berghahn, 2021)
"Don Handelman's groundbreaking work in anthropology is showcased in this collection of his most powerful essays, edited by Matan Shapiro and Jackie Feldman. The book looks at the intellectual and spiritual roots of Handelman's initiation into anthropology; his work on ritual and on "bureaucratic logic"; analyses of cosmology; and innovative essays on Anthropology and Deleuzian thinking. Handelman reconsiders his theory of the forming of form and how this relates to a new theory of the dynamics of time. This will be the definitive collection of articles by one of the most important anthropologists of the late 20th Century"--